Analisis Strategi Dalam Meningkatkan Jumlah Santri Di Pondok Pesantren Darul Ulum Ngulak - Delpio Ramadhony; Candra Darmawan; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2023)
This research is entitled: "Analysis of Strategies in Increasing the Number of Santri at the Darul Ulum Ngulak Islamic Boarding School, Sanga Desa District". This study aims to find out the strategy used by the Darul Ulum Islamic Boarding School in increasing the number of students. This research uses qualitative research. Data collection techniques in this study are using observation, interviews and documentation. The theory used is according to Kotler and Armstrong. The data analysis technique used in this study is data reduction, data presentation and conclusion or verification. The results of this study indicate that the promotional activities carried out by the Darul Ulum Ngulak Islamic Boarding School have gone quite well, promotional activities carried out by direct or indirect socialization, developing and optimizing extracurriculars and facilities or facilities and infrastructure. Evaluation of this activity Darul Ulum Ngulak Islamic Boarding School has increased every new school year, it's just that the target of students has not been achieved so far because most students are more interested in public schools. Suggestions for the Darul Ulum Ngulak Islamic Boarding School should have human resources that specifically control promotional activities to manage the interests of students or the public so that they can carry out promotions more optimally, so that they can operate promotional activities carried out so that they run well.